The Use of Evidence by Decision-Making Committees - Ali Soroush; Mohammad Mohseni; Saeed Komasi; Nadia Baharirad; Farideh Moradi (Baqiyatallah University of Medical Sciences, 2017)
By evidence, we mean systematic and extensive studies conducted to enhance knowledge and evidence-based policymaking (EBP), or evidence-based decision-making, an approach that helps individuals make decisions with more information and use the best evidence to establish, implement, and develop policies. Evidence-based policymaking is a complex of methods giving information to the process of policymaking rather than directly affecting the policies' probable goals. It is based on the idea that, in decision making, the existing information evidence should be exploited; moreover, the information used should have logical analysis. Hospital centers are the pillars of the health system in each country, and reforming the health sector without addressing such community centers and improving their performance would not be possible.